The metacognitive awareness of reading strategies amongst students of SMK Dato' Ibrahim Yaacob / Siti Zainab Kamaruddin - Kamaruddin, Siti Zainab (Faculty of Education, 2014)
This study investigated the metacognitive awareness of reading strategies that were used by the students in smk dato’ Ibrahim yaacob while reading academic texts, the relationship of their reading habits and their metacognitive awareness of reading strategies as well as the connection of their proficiency level and their used metacognitive awareness of reading strategies. There were 75 students that were participated in this study. These students were randomly chosen by the researcher according to their form, which were form 1 until form 5, with 15 of the students from each of the form. In order to determine the students’ use of metacognitive reading strategies, Metacognitive Awareness of Reading Strategies Inventory (MARSI) that was invented by Mohkhtari and Reichard, (2002), and The Canadian National Survey, (2005) of Reading and Buying Books for Pleasure’s questionnaire were used by the researcher in order to gain the data. The data were analyzed using the frequency, percentage and also the mean score. However in order to analyze the relationship of both variables and their use of metacognitive awareness of reading strategies, the regression was used by the researcher to gain the significant relationship between the dependent and independent variables. From this study it was found that most of the students have the average level of metacognitive awareness of reading strategies. Furthermore based from this study, it was also revealed that students’ reading habits does affect the use of metacognitive awareness of reading strategies by students. Students’ who have good reading habits have better use metacognitive awareness of reading strategies. In addition, according to this study, it is also proven that students’ proficiency level does affect the metacognitive awareness of reading strategies. Students with the higher level of proficiency have better use of metacognitive awareness of reading strategies.